2009
DOI: 10.1105/tpc.108.062596
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Protein Response as a Subcomponent of the Wider Heat Shock Response inArabidopsis 

Abstract: In common with a range of environmental and biological stresses, heat shock results in the accumulation of misfolded proteins and a collection of downstream consequences for cellular homeostasis and growth. Within this complex array of responses, the sensing of and responses to misfolded proteins in specific subcellular compartments involves specific chaperones, transcriptional regulators, and expression profiles. Using biological (ectopic protein expression and virus infection) and chemical triggers for misfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(230 citation statements)
references
References 44 publications
11
213
0
Order By: Relevance
“…The CPR is the cellular response corresponding to the accumulation of unfolded proteins in the cytoplasm, but not in the ER, and the UPR genes induced by Tm were excluded from the CPR genes (18). This observation can be interpreted as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPR is the cellular response corresponding to the accumulation of unfolded proteins in the cytoplasm, but not in the ER, and the UPR genes induced by Tm were excluded from the CPR genes (18). This observation can be interpreted as follows.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a cellular response different from the UPR occurs in the cytosol if protein folding in the cytosol is disturbed. This response is referred to as the cytosolic protein response (CPR) (17), and genes induced in the CPR in Arabidopsis were identified by microarray-excluding genes induced in the UPR (18). However, 30 of 190 genes up-regulated by Tm in ire1a/b were overlapped with the CPR genes, similar to the heat stress-responsive genes (Fig.…”
Section: Up-regulation Of Cytosolic Protein Response Genes In Ire1a/bmentioning
confidence: 99%
“…Several previous studies have concluded that misfolded proteins induce a subset of the heat-shock response in bacterial (17), fungal (35), plant (13,14), and vertebrate cells (40) by either monitoring transcript or protein changes in response to widespread misfolding (13,35) or monitoring only a handful of heatshock proteins (13,14,17,40). Recent studies have led to the proposal that the UPR-Cyto is a specific HSF1-mediated module of the eukaryotic heat-shock response (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…In the eukaryotic endoplasmic reticulum (ER), misfolded proteins provoke the unfolded protein response (UPR) (11), whereas in the cytosol, a broader heat-shock response combats protein misfolding, oxidative stress, altered membrane integrity, and reduced growth rate (12). Recent work suggests that the heat-shock response may mask a milder and more targeted response to counteract cytosolic protein misfolding (13)(14)(15), dubbed the UPR-Cyto (15), but the molecular components of this response remain unclear.…”
mentioning
confidence: 99%
“…The functional HSE element usually contains a minimum of three 5′nGAAn3′ repeated motifs with a maximum insertion of 5 bp between each motif. Sugio et al (2009) …”
Section: Introductionmentioning
confidence: 99%